The Spread of Commuter Development in the Eastern Shore Zone of Halifax, Nova Scotia, 1920-1988 - Millward, Hugh (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2000)
This study uses evidence from archival and recent topographic maps to plot developing patterns of commuter-induced residential construction in the Eastern Shore sector of the Halifax commuter zone. Building counts were made from 1:50,000 topographic maps surveyed in 1917–20 (pre-commuter situation), 1960–7 (early commuter), and 1988 (mature commuter), and the mapped patterns were analyzed visually and statistically.Both regionally and locally, a typical sequence of development is apparent and is discussed with examples. The evolving pattern of development has been moulded by five sets of variables: access, services, environment, socio-cultural factors, and planning. Some variables operate primarily at the regional scale (notably distance to the city centre), some at the district level (notably distance to an elementary school), and some are highly localized (e.g., the availability of road frontage). The results may be useful for anticipation and control of future development.